Bankruptcy rules and sustainable water management: A MODSIM-NSGAII simulation multi-objective optimization framework for equitable transboundary water allocation - Bentolhoda Asl-Rousta; S. Jamshid Mousavi (Environmental and Sustainability Indicators)
A primary challenge in shared or international water resources management is ensuring their ''equitable and reasonable utilization''. This issue is further complicated by scarcity and can be addressed using Bankruptcy Games (BG). Classical bankruptcy game methods assume homogenous resource accessibility, but water resource systems vary widely in both spatial and temporal dimensions. This study addresses these challenges by introducing a new optimal bankruptcy rule (OpPro rule) through a simulation-optimization model (MODSIM-NSGAII), where MODSIM simulates the spatial and temporal variability of water resources, and the NSGA-II optimization algorithm includes two objective functions of maximizing basin-wide ecological sustainability and maximizing economic efficiency reflecting ''equitable and reasonable utilization'' of water. A mechanism based on the rationality principle of cooperative games and the equity concept is designed to identify the most stable solution. Results indicate that the optimal bankruptcy coefficients for Iran and Iraq are 100 and 88, respectively, suggesting a 12% reduction in Iraq's agricultural water demands. Additionally, efficient water management practices and the cultivation of high-value agricultural products in Iraq are proposed to enhance the reasonable utilization of water in this country.